The case for thinking and working politically. The implications of 'do ing development differently' - DLP (DLP, 2014)
This paper discusses the steps required to build a robust evidence bas e for 'thinking and working politically' (TWP) in development. It argu es that better understanding what works, when and why is an important step in moving TWP into mainstream development programming. The paper reviews the existing evidence base on TWP, building on this and on oth er literature on public sector reform and 'pockets of effectiveness' t o suggest research questions, case study selection criteria, and a fou r-level analytical framework: 1) political context; 2) sector; 3) orga nisation; and 4) individual. The framework aims to help build a 'rigor ous enough' evidence base to show whether and how TWP happens and whet her or not it influences the effectiveness of programme implementation and outcomes. The paper also calls for more focus on gender issues, a nd on different – and often more fragile – political contexts.